Necrotizing fasciitis following transobturator tape procedure: a case report and literature review - Lee, Kwang Yeom; Sim, Jae Ang; Lee, Sheen Woo; Kim, Tae Beom; Yoon, San Jin; Park, Kyung Seo; Kim, Khae-Hawn (Canadian Urological Association Journal, 2013)
A 51-year-old diabetic woman was referred to our unit with a history of increasing pain in her right thigh and gait disturbance, 10 days following surgery for treatment of stress urinary incontinence with a transobturator tape. Examination elicited a tender right thigh associated with swelling and erythema. Inspection of the vagina revealed an exposed mesh through the vaginal erosion. Plain radiographs and magnetic resonance imaging revealed large thigh abscesses suggestive of gas gangrene from the pelvis to the calf. The mesh was completely removed; extensile incisions, as well as aggressive debridement of all necrotic tissue in the thigh and calf, were performed. A diagnosis of necrotizing fasciitis with gas extending to the lower leg level was confirmed. After mesh removal, abscess drainage and debridement, the patient recovered with antibiotics and daily wound care. Three months after the operation, the patient showed no recurrence of the infection.